ТЕОРЕТИЧНІ ЗАСАДИ ФОРМУВАННЯ ПРОФЕСІЙНО- ПЕДАГОГІЧНОЇ КУЛЬТУРИ МАЙБУТНЬОГО ПЕДАГОГА В ПЕРІОД ПЕДАГОГІЧНОЇ ПРАКТИКИ (Педагогіка вищої та середньої школи, 2004)
The problem of formation of the professional-pedagogical culture in the rip of the passing the pedagogical practice by students is examined in the article. Theoretic principles of treatment this problem are analyzed\ it is organized structure and levels its successful.